Diversity of Coral Reefs at Insrom Beach, Biak Numfor Regency - Eka Oviani Msen; Galuh P. W. Utami; Iriani Ira Bukorpioper (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2023)
ABSTRACTCoral reef represent tropical ecosystem encompassing a diverse marine biota associated with it. The aim if this study was to determine the types of coral reefs, diversity of coral reefs species, and the water quality on the Insrom coast. This study used a line transect method that stretched 50 meters in 3 stations at a depth of 3-5 meters. The results of this study indicated that there are 53 types of coral reefs. Overall diversity index (3.27). The water quality measurements yielded the following result: temperature 28-30oC, pH 7- 8- 2, salinity 30-32%, brightness ranging from 2.5-3 meters, current 3-8 m/sec, dissolved oxygen levels of 3-5 mg/l. The study’s conclusion is that there are 53 types of coral reefs. The insrom coast’s diversity index is 3.27 which shows high category according to Shannon-Wienner. The water quality of Insrom coast remains within tolerable range for the growth of coral reefs.Keywords: Diversity, Types, Coral reefs.